PERAN PEMBELAJARAN EKONOMI DALAM MEMBENTUK KESADARAN KONSUMEN MAHASISWA TERHADAP TRANSPARANSI PB1 DAN SERVICE CHARGE - Sri Asfiati; Anri Naldi; Zulkifli Siregar; Partaonan Harahap (STKIP Pesisir Selatan, 2026)
This study aims to analyze the role of economic learning in shaping students’ consumer awareness regarding the transparency of PB1 and service charges in cafés. The research employs a quantitative approach using a survey method involving 120 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics and simple linear regression. The results indicate that the average score of economic learning is 3.72 (good category), while consumer awareness is 3.65 (moderate–good category). The regression analysis shows that economic learning has a positive and significant effect on consumer awareness, with a regression coefficient of 0.48 and a t-value of 5.33 (>1.98). The coefficient of determination (R²) is 38.44%, indicating that economic learning contributes 38.44% to consumer awareness. The novelty of this study lies in its focus on the transparency of PB1 and service charges in students’ consumption behavior. These findings highlight the importance of contextual and applicable economic learning in enhancing students’ critical awareness as consumers.